Uromyces plumbarius first reported on Oenothera lindheimeri in Europe with widespread distribution and association with two common natural enemies of rust fungi - Frédéric Suffert; Kévin Meyer; Valérie Laval; Axelle Andrieux; Erik Slootweg; Pascal Frey (European Journal of Plant Pathology, 2026)

Approximate Bayesian Computation applied to time series of population genetic data disentangles rapid genetic changes and demographic variations in a pathogen population - Méline Saubin; Aurélien Tellier; Solenn Stoeckel; Axelle Andrieux; Fabien Halkett (Molecular Ecology, 2024)
Adaptation can occur at remarkably short timescales in natural populations, leading to drastic changes in phenotypes and genotype frequencies over a few generations only. The inference of demographic parameters can allow understanding how evolutionary forces interact and shape the genetic trajectories of populations during rapid adaptation. Here we propose a new Approximate Bayesian Computation (ABC) framework that couples a forward and individual‐based model with temporal genetic data to disentangle genetic changes and demographic variations in a case of rapid adaptation. We test the accuracy of our inferential framework and evaluate the benefit of considering a dense versus sparse sampling. Theoretical investigations demonstrate high accuracy in both model and parameter estimations, even if a strong thinning is applied to time series data. Then, we apply our ABC inferential framework to empirical data describing the population genetic changes of the poplar rust pathogen following a major event of resistance overcoming. We successfully estimate key demographic and genetic parameters, including the proportion of resistant hosts deployed in the landscape and the level of standing genetic variation from which selection occurred. Inferred values are in accordance with our empirical knowledge of this biological system. This new inferential framework, which contrasts with coalescent‐based ABC analyses, is promising for a better understanding of evolutionary trajectories of populations subjected to rapid adaptation.

A point mutation and large deletion at the candidate avirulence locus AvrMlp7 in the poplar rust fungus correlate with poplar RMlp7 resistance breakdown - Clémentine Louet; Méline Saubin; Axelle Andrieux; Antoine Persoons; Mathilde Gorse; Jérémy Pétrowski; Bénédicte Fabre; Stéphane De Mita; Sébastien Duplessis; Pascal Frey; Fabien Halkett (Molecular Ecology, 2023)
The deployment of plant varieties carrying resistance genes ( R ) exerts strong selection pressure on pathogen populations. Rapidly evolving avirulence genes ( Avr ) allow pathogens to escape R ‐mediated plant immunity through a variety of mechanisms, leading to virulence. The poplar rust fungus Melampsora larici ‐ populina is a damaging pathogen of poplars in Europe. It underwent a major adaptive event in 1994, with the breakdown of the poplar RMlp7 resistance gene. Population genomics studies identified a locus in the genome of M . larici ‐ populina that probably corresponds to the candidate avirulence gene AvrMlp7 . Here, to further characterize this effector, we used a population genetics approach on a comprehensive set of 281 individuals recovered throughout a 28‐year period encompassing the resistance breakdown event. Using two dedicated molecular tools, genotyping at the candidate locus highlighted two different alterations of a predominant allele found mainly before the resistance breakdown: a nonsynonymous mutation and a complete deletion of this locus. This results in six diploid genotypes: three genotypes related to the avirulent phenotype and three related to the virulent phenotype. The temporal survey of the candidate locus revealed that both alterations were found in association during the resistance breakdown event. They pre‐existed before the breakdown in a heterozygous state with the predominant allele cited above. Altogether, these results suggest that the association of both alterations at the candidate locus AvrMlp7 drove the poplar rust adaptation to RMlp7 ‐mediated immunity. This study demonstrates for the first time a case of adaptation from standing genetic variation in rust fungi during a qualitative resistance breakdown.

Exploring the role of asexual multiplication in poplar rust epidemics: impact on diversity and genetic structure - Benoît Barrès; Cyril Dutech; Axelle Andrieux; Fabien Halkett; Pascal Frey (Molecular Ecology, 2012)
Fungal plant pathogens, especially rust fungi ( P ucciniales), are well known for their complex life cycles, which include phases of sexual and asexual reproduction. The effect of asexual multiplication on population genetic diversity has been investigated in the poplar rust fungus M elampsora larici‐populina using a nested hierarchical sampling scheme. Four hierarchical levels were considered: leaf, twig, tree and site. Both cultivated and wild poplar stands were sampled at two time points at the start and end of rust epidemics. A total of 641 fungal isolates was analysed using nine microsatellite markers. This study revealed that the genetic signature of asexual multiplication in the wild poplar stand was seen only at lower hierarchical levels (leaf and twig). Moreover, we observed an erosion of clonal structure through time, with an increase in both gene and genotypic diversity. New genotypes contributed to host infection over time, which demonstrates the importance of allo‐infection in the epidemic process in this host‐pathogen system. Compared with the wild stands, the nearly lack of detection of clonal structure in the cultivated stands reflects the higher infection level on cultivated poplars. More generally, this genetic analysis illustrates the utility of population genetics approach for elucidating the proportion of asexual reproduction in the multiplication of isolates during an epidemic, and for proper quantification of asexual dispersal in plant pathogens.

Disentangling the genetic origins of a plant pathogen during disease spread using an original molecular epidemiology approach - CONSTANCE XHAARD; BENOÎT BARRÈS; AXELLE ANDRIEUX; LYDIA BOUSSET; FABIEN HALKETT; PASCAL FREY (Molecular Ecology, 2012)
The advent of molecular epidemiology has greatly improved our ability to identify the population sources and track the pathogen movement. Yet the wide spatial and temporal scales usually considered are useful only to infer historical migration pathways. In this study, Bayesian genetic assignments and a landscape epidemiology approach were combined to unravel genetic origin and annual spread during a single epidemic of a plant pathogen: the poplar rust fungus Melampsora larici‐populina . The study focused on a particular area—the Durance River valley—which enabled inoculum sources to be identified and channelled spread of the epidemic along a one‐dimensional corridor. Spatio‐temporal monitoring of disease showed that the epidemic began in the upstream part of the valley and spread out downstream. Using genetic assignment tests, individuals collected at the end of the epidemic were sorted into two genetic groups; very few hybrids were detected, although individuals from both groups coexisted locally downstream in the valley. The epidemic originated from two genetically distinct inoculum sources. Individuals of each group then dispersed southwards along the Durance River and became mixed in poplar riparian stands. These two genetic groups were found previously at a wider spatial scale and proved to result from distinct evolutionary histories on either wild or cultivated poplars. This study showed that the two groups can mix during an epidemic but do not hybridize because they then reproduce asexually. In general, the methods employed here could be useful for elucidating the genetic origin and retracing the colonization history and migration pathways of recent epidemics.

Characterization of 41 microsatellite loci developed from the genome sequence of the poplar rust fungus, Melampsora larici-populina - Constance Xhaard; Axelle Andrieux; Fabien Halkett; Pascal Frey (Conservation Genetics Resources, 2009)

SCAR–based PCR primers to detect the hybrid pathogen Phytophthora alni and its subspecies causing alder disease in Europe - Renaud Ioos; Claude Husson; Axelle Andrieux; Pascal Frey (European Journal of Plant Pathology, 2005)

Spontaneous chromosome circularization and amplification of a new amplifiable unit of DNA belonging to the terminal inverted repeats in Streptomyces ambofaciens ATCC 23877 - Sibel Catakli; Axelle Andrieux; Pierre Leblond; Bernard Decaris; Annie Dary (Archives of Microbiology, 2003)